1996
DOI: 10.1177/036354659602400616
|View full text |Cite
|
Sign up to set email alerts
|

What Best Protects the Inverted Weightbearing Ankle Against Further Inversion?

Abstract: We measured the maximal isometric eversion moment developed under full weightbearing in 20 healthy adult men (age, 24.4 ± 3.4 years; mean & p l u s m n ; SD) with their ankles in 15° of inversion. Tests were performed at both 0° and 32° of ankle plantar flexion in low-and in three-quarter-top shoes with and without adhesive athletic tape or one of three proprietary ankle orthoses. At 0° of ankle plantar flexion, the mean maximal voluntary resistance of the unprotected ankle to an invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…The peroneus muscles are the best protector against ankle inversion during foot strike 14) , and are important in stabilizing the ankle against lateral perturbation. However, Konradsen et al 15) reported that muscle reaction time was too slow to protect the ankle in case of sudden inversion occurring at the time of initial contact.…”
Section: Introductionmentioning
confidence: 99%
“…The peroneus muscles are the best protector against ankle inversion during foot strike 14) , and are important in stabilizing the ankle against lateral perturbation. However, Konradsen et al 15) reported that muscle reaction time was too slow to protect the ankle in case of sudden inversion occurring at the time of initial contact.…”
Section: Introductionmentioning
confidence: 99%
“…When the muscles contract, musculotendinous units generate stiffness, which serves as the dynamic restraint to joint movement [7]. The PB is integral to the control of supination of the rear foot [37]. The inability of the FAI subjects to exhibit proper control of the PB activity may have been due to a more abducted position of the ankle.…”
Section: Discussionmentioning
confidence: 99%
“…The strong peroneal activation recorded in this study was expected because of the combined tasks of balancing and eversion. Peroneal muscles are pivotal for ankle eversion and postural balance [2] [21], both of these functions are challenged while performing ankle eversion standing on one leg. HL exercise provoked less peroneal activity, likely due to the synergistic action of triceps surae group that partly mitigated the reliance on PL [22].…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical study indicates the prime importance of the PL strength in limiting ankle inversion as compared with mechanical barrier effect provided by various functional ankle orthoses and taping [2]. Optimal function of this evertor muscle depends on its strength [3], timely activation [4] [5], proprioception [6], and central modulation of motor control [7].…”
Section: Introductionmentioning
confidence: 99%